The Effect Of Service Quality On Customer Loyalty Mediated By Jne Express Customer Satisfaction In Bengkulu City - Rafles, Fadhlu Rohman Dian; Sari, Desti Rupita; Irwanto, Tito; Febliansa, M. Rahman (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
The purpose of this study was to determine the Analysis of the Effect of Service Quality on Consumer Loyalty Mediated by JNE Express Consumer Satisfaction in Bengkulu City. The type of research used is quantitative. The population in this study were all JNE Express consumers in Bengkulu City. The sampling technique used simple random sampling with a sample size of 150 people. Data collection techniques using questionnaires that have been tested for validity and reliability. The data analysis technique used to answer the hypothesis using SmartPLS 4 is the outer model, inner model and bootstrapping test. The results of this study indicate that: (1) service quality has a positive effect on customer satisfaction. This is evidenced by the t-statistic value of 5.362 which is greater than the t-table value (1.65) with a significance level of 0.000 (<0.05). (2) service quality has a negative effect on customer loyalty. This is evidenced by the t-statistic value of 1.340 which is smaller than the t-table value (1.65) with a level of significance of 0.192 exceeding the predetermined standard (<0.05). (3) customer satisfaction has a positive effect on customer loyalty. This is evidenced by the t-statistic value of 3.585 which is greater than the t-table value (1.65) with a significance level of 0.000 (<0.05). (4) service quality on customer loyalty mediated by customer satisfaction has a positive effect. This is evidenced by the mediation coefficient of the t-statistic value of 3.034 which is greater than the t-table value (1.65) with a significance level of 0.002 (<0.05).